Stem cell engineering principles and applications - Artmann, Gerhard M.; Minger, Stephen; Hescheler, Jürgen 1959- (Springer, 2011)
The potential of stem cells for healing and disease prevention in all fields of medicine is tremendous and has revolutionized the high-tech biomedical research. In this book, many of the most prominent researchers discuss the challenging topics of stem cell engineering, for example: Ethical issues of stem cell research; technological challenges, stem cell growth and differentiation, therapeutic applications, bioreactors and bioprocesses, high throughput and microfluidic screening platforms, stem cell identification and sorting, intercellular signaling and engineered niches, novel approaches for embryonic and adult stem cell growth and differentiation, stem cells and drug discovery, screening platforms. Stem Cell Engineering offers valuable background and reference for both the public and professionals including industrial staffers, faculty, researchers, engineers, students and scientific journalists.